Musik, Royalti, dan Konsumen: Analisis Kualitatif Pengaruh Kebijakan Hak Cipta di Pusat Perbelanjaan - Windarsari, Wiwin Riski (Politeknik Sawunggalih Aji, 2025)
Music is a crucial element in shaping public space atmospherics, particularly in shopping malls. It functions not only as entertainment but also as a strategic tool to influence consumer mood, comfort, and behavior. In Indonesia, the use of music in public spaces is regulated under Law No. 28 of 2014 on Copyright, which requires royalty payments to composers through the National Collective Management Organization (LMKN). This study aims to analyze the impact of music royalty policies on consumer behavior and shopping interest in shopping malls. A qualitative descriptive approach was employed using a case study design, involving in-depth interviews, direct observation, and document analysis. The findings reveal that most consumers perceive music as enhancing comfort, extending visit duration, and encouraging shopping interest. Respondents noted that slow-tempo music created a relaxed atmosphere, while fast-tempo music produced a more dynamic ambiance. Although most consumers were unaware of the royalty obligation, they supported the policy once explained, viewing it as protection for creators’ rights. Therefore, royalty policies should be considered not only as legal requirements but also as strategic investments that enhance shopping experiences while promoting the sustainability of the national music industry.